A novel ZZ/ZW sex chromosome system for the genus Leporinus (Pisces, Anostomidae, Characiformes) - Venere, P. C.; Ferreira, I. A.; Martins, C.; Galetti, P. M. (Kluwer Academic Publ, 2004)
A wide range of sex chromosome mechanisms, including simple and multiple chromosome systems is characteristic of fishes. The Leporinus genus represent a good model to study sex chromosome mechanisms, because an unambiguous ZZ/ZW sex chromosome system was previously described for seven species, while the remaining studied species of the genus do not show differentiated sex chromosomes. The occurrence of sex chromosomes in Leporinus trifasciatus and Leporinus sp2 from the Araguaia river, Amazon basin, Brazil, was here investigated. ZZ/ ZW sex chromosomes were detected for both species. The Z and W chromosome morphology of L. trifasciatus is the same as described for other species of the genus Leporinus. However, the Z and W chromosomes of L. sp2 were quite different in their morphology and banding pattern suggesting that the ZW system of this species have originated independently from the ZW system previously described for other Leporinus.
Keywords: chromosome; fish; Leporinus; sex chromosomes; ZZ/ZW system